Pharmacological Applications and Action Mechanisms of Phytochemicals as Alternatives to Antibiotics in Pig Production - Li, Lexing; Sun, Xueyan; Zhao, Dai; Dai, Hanchuan (Frontiers in Immunology, 2021)
Antibiotics are widely used for infectious diseases and feed additives for animal health and growth. Antibiotic resistant caused by overuse of antibiotics poses a global health threat. It is urgent to choose safe and environment-friendly alternatives to antibiotics to promote the ecological sustainable development of the pig industry. Phytochemicals are characterized by little residue, no resistance, and minimal side effects and have been reported to improve animal health and growth performance in pigs, which may become a promising additive in pig production. This paper summarizes the biological functions of recent studies of phytochemicals on growth performance, metabolism, antioxidative capacity, gut microbiota, intestinal mucosa barrier, antiviral, antimicrobial, immunomodulatory, detoxification of mycotoxins, as well as their action mechanisms in pig production. The review may provide the theoretical basis for the application of phytochemicals functioning as alternative antibiotic additives in the pig industry.